2022
DOI: 10.1029/2020jd033761
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Hemispheric Coupling During Sudden Stratospheric Warming Events With Elevated Stratopause

Abstract: The Earth's atmosphere is highly coupled internally among the different vertical layers and geographical regions, and externally with oceans, land, and space (Yiğit & Medvedev, 2015). Sudden stratospheric warmings (SSW) occur in the winter-time polar stratosphere during which the temperature increases substantially (∼20-30 K) and are accompanied by a stratospheric zonal wind reversal in the high latitude/polar region. SSW are a result of interaction between upward propagating planetary waves and the zonal mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…It is also worth noting that warm anomalies greater than 2 K are observed in the southern upper mesosphere around z = 80 km in 40°S-90°S. This feature is consistent with the IHC associated with the Arctic SSW indicated by previous studies (e.g., Karlsson, McLandress, et al, 2009;Naren Athreyas et al, 2022;Yasui et al, 2021).…”
Section: Time-height Section Of Zonal-mean Zonal Windsupporting
confidence: 90%
See 1 more Smart Citation
“…It is also worth noting that warm anomalies greater than 2 K are observed in the southern upper mesosphere around z = 80 km in 40°S-90°S. This feature is consistent with the IHC associated with the Arctic SSW indicated by previous studies (e.g., Karlsson, McLandress, et al, 2009;Naren Athreyas et al, 2022;Yasui et al, 2021).…”
Section: Time-height Section Of Zonal-mean Zonal Windsupporting
confidence: 90%
“…Such a remote response is inferred to be caused by the modulation of the meridional circulation, driven by wave forcing and its interaction with the mean flow over the two hemispheres (e.g., Körnich & Becker, 2010; Murphy et al., 2012; Naren Athreyas et al., 2022; Yasui et al., 2021). Körnich and Becker (2010), hereafter referred to as KB10, proposed a simple and compelling scenario for the IHC and demonstrated it using an axisymmetric model that included gravity wave (GW) parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of UA-ICON, the 25 km threshold results in too few ESEs and therefore we reduced this threshold to 18 km. Nevertheless, even with the reduced threshold, we found approximately two ESEs per decade in UA-ICON (CTL simulation) which is less than the observed frequency of ESEs (3.5 events per decade in MLS observations (Naren Athreyas et al, 2022)). The annual frequency of ESEs was reported between 28% and 36% in four 53-year simulations by WACCM .…”
Section: Analysis Methodscontrasting
confidence: 77%
“…For example, Manney et al (2008) have shown that MERRA reanalyses are unable to capture the rise of the stratopause to very high altitudes during ESEs. With the improvements in the spatial and temporal resolutions of middle and upper atmospheric satellite data, detailed analyses of ESEs have become feasible in recent years (France, Harvey, Alexander, et al, 2012;Manney et al, 2008;Naren Athreyas et al, 2022;Orsolini et al, 2010;Shi et al, 2022). Modeling studies with WACCM (France & Harvey, 2013;Limpasuvan et al, 2016;Orsolini et al, 2017), the Canadian Middle Atmosphere Model (CMAM; McLandress et al, 2013), a high-resolution middle atmosphere GCM developed for the KANTO project (Tomikawa et al, 2012), the ECHAM/MESSy Atmospheric Chemistry (EMAC; Scheffler et al, 2022) and with the Japanese Atmospheric General circulation model for Upper Atmosphere Research (JAGUAR, Okui et al (2021)) provided insights into the sequence of events associated with the occurrence of a typical ES event.…”
mentioning
confidence: 99%
“…Athreyas et al. (2022) further found that during major SSW events with elevated stratopause, the polar summer mesopause cools during the stratospheric warming phase and warms during the stratopause discontinuity and reformation phases.…”
Section: Introductionmentioning
confidence: 97%